Oxidative stress in plants and the biochemical response mechanisms - Borges, Cristine Vanz [UNESP]; Orsi, Ricardo Oliveira [UNESP]; Maraschin, Marcelo; Lima, Giuseppina Pace Pereira [UNESP] (Elsevier, 2023)
The accumulation of reactive oxygen species (ROS) caused by abiotic or biotic stresses generates oxidative stress in plant cells. To prevent the spread or to stop this chain reaction, antioxidant systems are activated, transforming free radicals (oxidants) into less toxic molecules for the cells. These generated antioxidant compounds can reduce the harmful effects of ROS and are classified as enzymatic (superoxide dismutase, peroxidases, catalase, among others) and nonenzymatic (bioactive amines, phenolic and carotenoid compounds). These molecules are essential to avoid damage to cell structures and cell death. In this chapter, we will present the response of plants under stress, activating some enzymatic systems and bioactive compounds (nonenzymatic), in order to alleviate oxidative stress.
Keywords: Antioxidant enzyme; biogenic amines; carotenoids; phenolic compounds